Предмет: Алгебра,
автор: няяшкааа
Знайдіть значення виразу 3^0+3^(-4)∙(3^(-2) )^(-3)-(0,5)^(-2)
Ответы
Автор ответа:
0
3^0=1
3^(-4)=1/3^4=1/81
(3^(-2))^(-3)=(1/9)^(-3)=81*9
0,5^(-2)=(1/2)^(-2)=4
1+(1/81)*81*9-4=1+9-4=6
3^(-4)=1/3^4=1/81
(3^(-2))^(-3)=(1/9)^(-3)=81*9
0,5^(-2)=(1/2)^(-2)=4
1+(1/81)*81*9-4=1+9-4=6
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: chipaet
Предмет: Музыка,
автор: asteriskchan
Предмет: Математика,
автор: Аноним
Предмет: Литература,
автор: radshabova1987